2020
DOI: 10.1093/humrep/dez300
|View full text |Cite
|
Sign up to set email alerts
|

Do physical activity, sitting time and body mass index affect fertility over a 15-year period in women? Data from a large population-based cohort study

Abstract: STUDY QUESTION Do physical activity (PA), sitting time (ST) and body mass index (BMI) affect fertility over a 15-year period in Australian women? SUMMARY ANSWER Moderate and high levels of PA confer advantages for fertility in women with normal BMI, but increased risk of infertility was observed in obese women. WHAT IS KNOWN ALREADY Higher BMI is positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…If our projections are ratified, the health effects for our millennial cohort will be profound. With average BMI in the obese category, there will be increases in 'mainstream' NCDs such as CVD, diabetes, cancers, osteo-arthritis and mental health problems, and in numerous less frequently cited consequences of obesity such as incontinence, cataracts, and reproductive health problems [15,[29][30][31][32]. This will mean increased health care costs, as previous analyses of ALSWH data have already shown that health care costs are significantly higher for women in the obese BMI category until at least 78 years of age, and that Australian women with obesity have almost twice the number of prescriptions and higher pharmaceutical costs across the lifespan than women with healthy weight [33].…”
Section: Discussionmentioning
confidence: 99%
“…If our projections are ratified, the health effects for our millennial cohort will be profound. With average BMI in the obese category, there will be increases in 'mainstream' NCDs such as CVD, diabetes, cancers, osteo-arthritis and mental health problems, and in numerous less frequently cited consequences of obesity such as incontinence, cataracts, and reproductive health problems [15,[29][30][31][32]. This will mean increased health care costs, as previous analyses of ALSWH data have already shown that health care costs are significantly higher for women in the obese BMI category until at least 78 years of age, and that Australian women with obesity have almost twice the number of prescriptions and higher pharmaceutical costs across the lifespan than women with healthy weight [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many women trying to conceive lead unhealthy lifestyles that affect their chances of becoming pregnant ( 7 , 8 ). Risk factors include poor diet ( 9 , 10 ), being overweight or obese, a sedentary lifestyle ( 11 ), tobacco use, and high levels of anxiety or depression ( 12 ), among others ( 13 ). Moreover, women's pre-conception lifestyle can not only decrease natural fertility, but also affect the results of fertility treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Among overweight/obese women (BMI ≥25 kg/m 2 ), fecundability was 27% higher for vigorous PA of ≥5 versus <1 h/week (Figure 3) [151]. In another cohort study, analyzing Australian women over a 15-years period, a lower risk of fertility issues was observed in the highly active and normal weight women, while a higher risk was observed in the obese women [152].…”
Section: Physical Activitymentioning
confidence: 96%